EVALUATION OF LAND USE WITH REGIONAL SPATIAL PLAN (RTRW) USING SATELLITE DATA AND GIS IN BATUR UNESCO GLOBAL GEOPARK - Putu Wira Utama; Takahiro Osawa; I Wayan Sandi Adnyana (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2018)
Development in ??Batur UNESCO Global Geopark which has an area of ??19,422.39 ha has increased significantly in recent years. The existence of limited land and to know the suitability of land use, it is necessary to evaluate of land use with regional spatial plan (RTRW). Landsat 8 satellite remote sensing data on 27 September 2017 is used to create land use maps. Land use maps obtained through the process of image classification using supervised classification method and verified by ground check. From this technique result 11 classes of land use. Furthermore, to evaluate of land use suitability was conducted by comparing land use with regional spatial plan (RTRW). In this process, there is an overlay between the land use maps with regional spatial plan (RTRW) map using geographic information system (GIS). The results of evaluation land use in Batur UNESCO Global Geopark with regional spatial plan (RTRW) overall has suitable area 10,863.14 ha (55.93%), not suitable area 8,275.58 ha (42.61%) and not detected/cloud interference 283.67 ha (1.46%).